FORMULASI KRIM DARI EKSTRAK AIR DAUN ALPUKAT (Persea americana Mill.) SEBAGAI SEDIAAN ANTI JERAWAT - Wilda Wildani; nofriyanti nofriyanti (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Acne is a common skin condition in the community. Inflammation of acne can be caused by the bacteria Propionibacterium acne, Staphylococcus epidermidis, Staphylococcus aureus. Cream is a form of acne preparations that circulate on the market, usually cream contains various chemicals, one of the side effects can irritate the skin, thus it is necessary to solution the use of materials from plants that are as antibacterial. One of the herbs that have been scientifically proven to contain antibacterial agents and that can be used to treat acne is Avocado leaves (Persea americana Mill.). This study aims to form the water extract of avocado leaf (Persea americana Mill.) To be formulated in a stable anti-acne cream preparation and can inhibit the bacteria Staphylococcus aureus. Formulation of avocado leaves water extract cream was made at concentrations of 12.5%, 15%, 17.5%, 20%. The results of this study indicate that the cream of avocado leaves water extract is good and physically stable for 4 weeks of storage, and is effective as an anti-acne. It is expected that this study will provide information that the natural ingredients of avocado leaves can inhibit the bacteria Staphylococcus aureus as the cause of acne bacteria.